Anti-corrosion construction method for offshore wind power foundation

By constructing a composite system on the offshore wind power foundation structure consisting of a self-healing zinc-aluminum alloy underlayer, a graphene-reinforced epoxy micaceous iron oxide intermediate layer, and a high-intensity pulsed light-cured top layer, the problem of early failure of traditional coatings in harsh environments has been solved, achieving efficient self-healing and uniform curing, and meeting the design life requirements of wind farms.

CN121198566APending Publication Date: 2025-12-26CHINA HARBOUR ENGINEERING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511462441.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-14
Publication Date
2025-12-26

AI Technical Summary

Technical Problem

Traditional coating systems are difficult to maintain long-term protective effects in the splash zone and fully immersed zone of offshore wind power foundations under harsh environments, and are prone to problems such as early failure, pitting corrosion, and peeling. Furthermore, it is difficult to achieve uniform curing and rapid evaluation of anti-corrosion performance during the construction process.

Method used

A composite system consisting of a self-healing zinc-aluminum alloy base layer, a graphene-reinforced epoxy micaceous iron oxide intermediate layer, and a high-intensity pulsed light-cured top layer is adopted. By combining microencapsulation technology, atomic layer deposition, and specific photocuring parameters, a dense coating is formed, which enhances adhesion and self-healing ability. Non-destructive testing is performed using electrochemical impedance spectroscopy.

Benefits of technology

It significantly improves the coating's self-healing ability after mechanical damage and its barrier effect against corrosive media, extends its anti-corrosion life, ensures the stability and integrity of the coating in harsh environments, and meets the 25-year design life requirement of wind farms.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to an anti-corrosion construction method for an offshore wind power foundation, belongs to the technical field of ocean engineering anti-corrosion, and solves the technical problem that the anti-corrosion service life of a foundation structure cannot meet the design requirement of a wind power plant due to the fact that a traditional single coating system is prone to early failure, pitting corrosion and stripping in a severe ocean environment, especially in a splash zone and a tidal range zone. The method comprises the following steps: carrying out sand blasting treatment on the outer surface of the steel structure until the cleanliness is Sa2.5 level and the roughness Ry is 60-100 microns; spraying a zinc-aluminum alloy bottom layer containing repairing microcapsules in the splash zone and the total immersion zone in an electric arc manner; coating an epoxy micaceous iron interlayer added with 0.5-1.5% of functionalized graphene oxide, wherein the thickness of the epoxy micaceous iron interlayer is 300-450 [mu] m; and finally, coating a fluorocarbon resin or polysiloxane surface layer, and scanning and curing by adopting intense pulsed light at the energy density of 5-15J / cm and the pulse width of 1-5ms. The method is mainly used for improving the long-term protection performance and prolonging the service life of the offshore wind power foundation structure in the corrosion environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of marine engineering corrosion protection technology. More specifically, this invention relates to a method for corrosion protection construction of offshore wind turbine foundations. Background Technology

[0002] Offshore wind turbine foundations are exposed to harsh marine corrosion environments for extended periods, and the performance of their anti-corrosion coatings directly impacts the design life and operational safety of the entire wind farm. Currently, these structures typically employ a composite coating system with an epoxy zinc-rich or metal-sprayed base layer, an epoxy micaceous iron oxide intermediate layer, and a fluorocarbon or polysiloxane top layer for protection. However, in practical applications, particularly in the most corrosive areas such as splash zones and tidal zones, traditional coating systems still exhibit several limitations, making it difficult to consistently guarantee a protective effect matching the 25-year design life of the wind farm.

[0003] The main problems are concentrated in early failure of the coating system, localized pitting corrosion, and coating peeling. The splash zone is subjected to the combined effects of multiple factors, including periodic wetting by seawater, strong ultraviolet radiation, alternating wet and dry conditions, and the mechanical impact of waves, posing a significant challenge to the coating's adhesion, corrosion resistance, and durability. In this area, corrosion products of traditional zinc-aluminum coatings may gradually accumulate and expand in volume, leading to increased internal stress and consequently a decrease in the adhesion between the substrate and the underlying material. Furthermore, if the coating develops micro-cracks or damage due to impact during transportation, installation, or service, corrosive media can rapidly penetrate the metal substrate, causing localized corrosion, which may propagate as undercoating corrosion, ultimately leading to blistering and large-area peeling.

[0004] For fully immersed zones, although environmental factors are relatively stable, long-term hydrostatic pressure, microbial adhesion, and ocean currents still place high demands on the integrity and shielding performance of the coating. Traditional coatings with microscopic defects or curing shrinkage stress can provide pathways for the penetration of corrosive media such as chloride ions.

[0005] To address these issues, the industry has attempted various methods, such as increasing the total coating thickness, optimizing the formulation to increase filler content, or using more corrosion-resistant metallic coatings. However, these methods also face new challenges. Simply increasing the coating thickness may introduce greater internal stress and increase sensitivity to the quality of the substrate surface treatment; modified coatings need to balance their application performance, interlayer compatibility, and long-term stability. More importantly, achieving rapid self-sealing of damaged areas in harsh environments and effectively delaying the lateral penetration of media along coating defects or interlayer interfaces are key challenges in improving the long-term corrosion resistance of coating systems.

[0006] Furthermore, the short construction window, high humidity, and variable temperature at sea pose additional limitations on the on-site curing of coatings and the final film quality. Traditional thermosetting or natural curing methods may fail to achieve complete cross-linking and optimal performance of the coating under certain conditions, affecting the reliability of the overall protective effect of the coating system.

[0007] Therefore, there is an urgent need to develop an anti-corrosion construction method for offshore wind power foundations, particularly suitable for the harsh conditions of splash zone and full immersion zone. This method should be able to effectively improve the overall adhesion, impact resistance, long-term shielding and self-repair capability of the coating system, thereby significantly extending the protection life. Summary of the Invention

[0008] One object of the present invention is to solve at least the above-mentioned problems and to provide at least the advantages that will be described later.

[0009] Another objective of this invention is to provide a method for corrosion protection construction of offshore wind power foundations. This method aims to solve the technical problem that traditional composite coating systems are prone to early failure, pitting, and peeling due to the penetration of corrosive media, mechanical damage, and insufficient curing in harsh marine environments, especially in splash zones and tidal zones. This makes it difficult for their corrosion protection life to match the 25-year design life of wind farms.

[0010] Another objective of this invention is to address the key technical challenges of effectively combining repair microcapsules with metal coatings, ensuring that the microcapsules maintain structural integrity and functional activity in the high-temperature, high-speed jet of high-speed arc spraying, and improving the bonding strength between the filler and the coating substrate, in order to prepare a metal substrate with highly efficient self-healing function.

[0011] Another objective of this invention is to address the technical problems that may lead to insufficient bonding between porous arc-sprayed coatings and subsequent organic coatings due to differences in interfacial penetration and compatibility, and that residual pores may become preferential channels for the penetration of corrosive media.

[0012] Another objective of this invention is to address the problem of improving the interfacial bonding force between the top layer and the intermediate layer, and how to stimulate the surface activity of the intermediate layer through pretreatment, thereby promoting the cross-linking and curing of the top layer resin, and ultimately enhancing the interlayer adhesion and overall density of the entire coating system.

[0013] Another objective of this invention is to address the technical problem that the two fillers with different properties, repair microcapsules and graphene-modified zinc-aluminum powder, are prone to uneven dispersion during mechanical mixing, and the interfacial bonding between them is weak, which may affect the synergistic effect of the composite filler in the coating.

[0014] Another objective of this invention is to solve the technical problem of poor interfacial compatibility and weakened adhesion that may exist between the epoxy micaceous iron oxide intermediate layer and the fluorocarbon or polysiloxane top layer due to differences in chemical properties.

[0015] Another objective of this invention is to address the technical problems of how substandard or uneven surface roughness affects the mechanical interlocking force and adhesion strength between the coating and the substrate, and how to quantitatively control and verify the surface profile after sandblasting to meet the optimal coating bonding conditions.

[0016] Another objective of this invention is to address the technical problem of how to precisely control the thickness and uniformity of the insulating protective film when surface-modifying composite fillers using atomic layer deposition technology, so as to achieve a balance between effective electrochemical protection and over-corrosion protection.

[0017] Another objective of this invention is to address the technical problem of how to ensure that the coating system, especially thick films and shaded areas, can be fully and uniformly cured to achieve optimal performance when selecting the energy parameters and scanning methods of strong pulsed light during on-site construction of complex components.

[0018] Another objective of this invention is to address the technical problem of how to quickly, non-destructively, and quantitatively assess the integrity and effectiveness of the anti-corrosion performance on-site after the coating application is completed, and to promptly identify and locate potential defect areas.

[0019] To achieve these objectives and other advantages of the present invention, a method for corrosion protection construction of offshore wind turbine foundations is provided, comprising the following steps: Step 1: Sandblast the outer surface of the offshore wind power foundation steel structure to remove rust, achieving a cleanliness level of Sa2.5 and a surface roughness of Ry60~100μm; Step 2: Apply a self-healing zinc-aluminum alloy underlayer to the splash zone and full immersion zone of the pretreated steel structure. This underlayer is formed by high-speed arc spraying of a composite filler containing repair microcapsules together with zinc-aluminum alloy wire. The spraying thickness is 200-350μm. The composite filler containing repair microcapsules is composed of microcapsules coated with corrosion inhibitors and graphene-modified zinc-aluminum powder. Step 3: Coat an epoxy micaceous iron oxide intermediate layer onto the zinc-aluminum alloy base layer. The coating of the epoxy micaceous iron oxide intermediate layer contains functionalized graphene oxide sheets that have been modified by a silane coupling agent. The amount of graphene oxide added is 0.5% to 1.5% of the total mass of the epoxy micaceous iron oxide coating. The thickness of the epoxy micaceous iron oxide intermediate layer is 300 μm to 450 μm. Step 4: Apply a fluorocarbon resin or polysiloxane topcoat to the epoxy micaceous iron oxide intermediate layer, with a thickness of 80-150 μm; after the topcoat is applied, use a portable high-intensity pulsed light curing device to scan and cure the coating system. The energy density of the high-intensity pulsed light is 5-15 J / cm², and the pulse width is 1-5 ms.

[0020] Preferably, the preparation method of the composite filler containing repair microcapsules of the present invention specifically comprises: S1. Using the sharp-hole coagulation bath method, sodium alginate aqueous solution containing fluorinated ceric acid corrosion inhibitor is used as the core material, and an organic solution of pH-responsive polymer is used as the wall material. The core material and wall material are dripped together into a calcium chloride coagulation bath through a dual-channel nozzle to form a microcapsule preform. The microcapsule preform is then transferred to an acetic acid solution, and the wall material is further solidified and cross-linked through interfacial polymerization. After washing and freeze-drying, spherical repair microcapsules are obtained. S2. Using chemical vapor deposition, zinc-aluminum alloy powder is heated to 500-800℃ in a fluidized bed reactor, and carbon-containing precursor gas is introduced. The carbon atoms generated by the cracking of the carbon-containing precursor gas are deposited and graphitized on the surface of the powder particles by the catalytic effect of the zinc-aluminum alloy powder, forming a graphene-coated composite powder. S3. The repair microcapsules obtained in step S1 and the graphene-modified zinc-aluminum powder obtained in step S2 are mechanically mixed at a mass ratio of 1:8~15. After mixing, an amorphous alumina film with a thickness of 5~20nm is uniformly deposited on the surface of the mixed composite filler using atomic layer deposition technology. The composite filler, after ALD treatment, is fed into the jet of a high-speed electric arc spray gun simultaneously with the zinc-aluminum alloy wire through a powder feeder, and together they are deposited to form a self-healing zinc-aluminum alloy composite underlayer.

[0021] Preferably, before coating the epoxy micaceous iron oxide intermediate layer in step three, the self-healing zinc-aluminum alloy substrate is sealed. Specifically, a nano-silica sol penetrating liquid diluted to a solid content of 15-25% is applied to the surface of the self-healing zinc-aluminum alloy substrate using an airless spraying process to form a transition layer with a thickness of 5-15 μm. The nano-silica sol has a particle size range of 10-20 nm and a pH value of 8.5-9.5. The transition layer is forced to dry at 50-60°C for 10-15 minutes before coating the epoxy micaceous iron oxide intermediate layer.

[0022] Preferably, in step four of the present invention, after the surface coating is completed and before scanning and curing using a portable intense pulsed light curing device, a pulsed ultraviolet laser beam with a wavelength of 355-405 nm is used to scan the coating surface at a scanning speed of 10-50 mm / s and a pulse frequency of 5-20 kHz, with the laser energy density controlled at 50-150 mJ / cm²; the scanning path of the pulsed ultraviolet laser beam forms an angle of 45-90° with the scanning path of the subsequent intense pulsed light curing device.

[0023] Preferably, the specific process of mechanical mixing in step S3 of the present invention is as follows: the repair microcapsules obtained in step S1 and the graphene-modified zinc-aluminum powder obtained in step S2 are placed in a high-speed mixer, heated to 50-70°C and stirred; then, 0.5-2.0% of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, accounting for 0.5-2.0% of the total mass of the composite filler, is dissolved in anhydrous ethanol to prepare a solution, and sprayed into the mixer in the form of atomization, and stirred at 50-70°C for 30-60 minutes.

[0024] Preferably, after step three is completed and before step four begins, the surface of the epoxy micaceous iron oxide intermediate layer is treated with a silane coupling agent. Specifically, the silane coupling agent is diluted to a 1-3% aqueous solution, applied to the surface of the epoxy micaceous iron oxide intermediate layer by spraying, and left to stand for 5-10 minutes before the topcoat is applied.

[0025] Preferably, in step one of the present invention, after sandblasting to remove rust and before applying the base coat, a non-contact three-dimensional surface profilometer is used to detect the surface roughness. If the Ry value does not reach the range of 60-100μm, sandblasting is repeated until the standard is met. The abrasive used for sandblasting is a mixture of steel grit and steel shot, with a mixing mass ratio of 7:3, an abrasive hardness of HRC 40-50, and a particle size range of 0.5-1.2mm.

[0026] Preferably, in step S3 of the present invention, the specific process parameters for depositing amorphous alumina thin films using atomic layer deposition technology are as follows: trimethylaluminum and water are used as precursors, the deposition temperature is 100-150°C, the reaction chamber pressure is 100-300 Pa, the aeration time for each ALD cycle is 0.5-1.5 s, the purification time is 5-10 s, and the number of cycles is 50-200.

[0027] Preferably, in step four of the present invention, the operating parameters of the portable intense pulsed light curing device further include: a pulse spectrum range of 300–800 nm, a cooling time interval of 2–5 s after a single pulse, a working distance of 10–15 cm between the scanning head and the coating surface, and a scanning overlap rate of 30–50%.

[0028] Preferably, after all coating application and curing is completed, electrochemical impedance spectroscopy is used to perform non-destructive testing on the coating system, with a test frequency range of 10. 5 ~10 -2 The applied AC disturbance signal amplitude is 20mV; if the impedance modulus |Z| measured at a frequency of 0.01Hz is less than 1×10⁻⁶, the disturbance signal amplitude is 20mV. 8 If the value is Ω·cm², then the coating in that area is considered defective and needs to be marked and recoated.

[0029] The present invention has at least the following beneficial effects: 1. This invention significantly improves the coating's self-healing ability after mechanical damage, its barrier effect against corrosive media penetration, and its interlayer bonding strength by constructing a composite system comprising a self-healing metal underlayer, a graphene-reinforced intermediate layer, and a high-performance surface layer cured by intense pulsed light, thereby effectively extending its anti-corrosion life in harsh environments such as splash zones.

[0030] 2. This invention uses a pH-responsive wall material corrosion inhibitor, prepares graphene-modified powder using CVD to enhance corrosion resistance, and finally deposits an ultra-thin alumina film using ALD. This effectively protects the activity of microcapsules during the spraying process, improves the dispersibility and binding of fillers, and ensures the long-lasting self-healing function and electrochemical protection of the underlying coating.

[0031] 3. The sealing treatment of this invention utilizes the low viscosity and high permeability of nano-silica sol to effectively seal the micropores on the surface of the metal spray coating, forming a dense inorganic transition layer. This not only prevents the medium from reaching the substrate directly, but also significantly improves the adhesion and compatibility with subsequent organic coatings.

[0032] 4. This invention utilizes ultraviolet laser with specific parameters to clean and activate the coating surface, effectively removing contaminants and generating active groups. At the same time, it may produce fine textures to increase the surface area, thereby enhancing the mechanical interlocking and chemical bonding between the top layer and the intermediate layer, improving the energy absorption and penetration of strong pulsed light, and promoting the overall curing effect.

[0033] 5. This invention modifies the surface by heating and adding a silane coupling agent solution, which promotes uniform dispersion and tight encapsulation between the two filler particles and may form chemical bridges at the interface, enhancing the integrity of the composite filler and enabling it to perform its respective functions more stably and uniformly in the coating.

[0034] 6. This invention forms a molecular bridge with bidirectional reactivity by adsorbing and hydrolyzing a silane coupling agent on the surface of the intermediate layer. On the one hand, the bridge binds to the hydroxyl groups on the surface of the intermediate layer, and on the other hand, it reacts with the functional groups of the surface resin, thereby greatly enhancing the chemical bonding force and hydrolytic stability between the epoxy micaceous iron oxide intermediate layer and the surface layer.

[0035] 7. The quality control measures of this invention ensure that the substrate surface forms a uniform profile with the best anchoring effect by accurately quantifying the surface roughness and selecting an appropriate abrasive ratio, thus providing the foundation for the maximum mechanical adhesion of the coating and guaranteeing the long-term stability of the coating system from the source.

[0036] 8. By precisely controlling the reaction temperature, pressure, time and number of cycles of ALD, this invention can form a nano-thickness and completely cover the surface of complex-shaped composite fillers. This film can provide good electrical insulation to prevent excessive consumption of zinc-aluminum fillers without significantly affecting their necessary cathodic protection function.

[0037] 9. The parameter settings of this invention optimize spectral matching, energy control and scanning strategy to ensure that the strong pulse light energy can penetrate the surface layer and effectively trigger the curing reaction of the intermediate layer and transition layer, while avoiding coating blistering or aging caused by overheating. It is suitable for uniform and efficient curing of complex shapes and thick film systems in the on-site construction of large structures.

[0038] 10. The quality assessment method of this invention can quickly and quantitatively assess the integrity and shielding performance of the coating system through on-site non-destructive testing. It can effectively identify early defects or potential failure areas through the sensitive indicator of low-frequency impedance modulus, providing a scientific basis for timely maintenance and ensuring the overall quality of anti-corrosion projects.

[0039] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Detailed Implementation

[0040] The present invention will be further described in detail below with reference to embodiments, so that those skilled in the art can implement it based on the description.

[0041] It should be understood that terms such as “having,” “comprising,” and “including” as used herein do not exclude the presence or addition of one or more other elements or combinations thereof.

[0042] It should be noted that, unless otherwise specified, the experimental methods described in the following implementation plan are all conventional methods, and the reagents and materials described are all commercially available unless otherwise specified.

[0043] In one embodiment of the present invention, a method for corrosion protection construction of offshore wind power foundations is provided, comprising the following steps: Step 1: Sandblast the outer surface of the offshore wind power foundation steel structure to remove rust, achieving a cleanliness level of Sa2.5 and a surface roughness of Ry60~100μm; Step 2: Apply a self-healing zinc-aluminum alloy underlayer to the splash zone and fully immersed zone of the pretreated steel structure. This underlayer is formed by high-speed arc spraying of a composite filler containing repair microcapsules together with zinc-aluminum alloy wire. The spraying thickness is 200-350 μm. The composite filler containing repair microcapsules is composed of microcapsules coated with corrosion inhibitors and graphene-modified zinc-aluminum powder. The repair microcapsules are uniformly distributed in the coating, with an areal density of 500-2000 capsules / mm². Step 3: Coat an epoxy micaceous iron oxide intermediate layer onto the zinc-aluminum alloy base layer. The coating of the epoxy micaceous iron oxide intermediate layer contains functionalized graphene oxide sheets modified with a silane coupling agent. The amount of graphene oxide added is 0.5% to 1.5% of the total mass of the epoxy micaceous iron oxide coating. The thickness of the epoxy micaceous iron oxide intermediate layer is 300 to 450 μm. The functionalized graphene oxide is graphene oxide modified with a silane coupling agent KH-560. Its surface contains epoxy groups, which can enhance the compatibility and chemical bonding with epoxy resin. Step 4: Coat the epoxy micaceous iron oxide intermediate layer with a fluorocarbon resin or polysiloxane top layer with a thickness of 80-150 μm; after the top layer is coated, use a portable high-intensity pulsed light (IPL) curing device to scan and cure the coating system. The energy density of the high-intensity pulsed light is 5-15 J / cm², and the pulse width is 1-5 ms.

[0044] This embodiment relates to a method for corrosion protection construction of offshore wind power foundations. Its core steps include: sandblasting pretreatment, coating a self-healing zinc-aluminum alloy underlayer, coating a graphene-reinforced epoxy micaceous iron oxide intermediate layer, coating a top layer, and curing with intense pulsed light (IPL). The sandblasting treatment uses a mixture of steel grit and steel shot, with a hardness of HRC 40-50 and a particle size of 0.5-1.2 mm. Using sandblasting equipment such as a pressure sandblasting machine, the outer surface of the steel structure is treated to achieve a cleanliness level of Sa2.5 and a roughness Ry value controlled at 60-100 μm. Subsequently, in the splash zone and fully immersed zone, a high-speed arc spraying device, such as the SX-500 arc spraying system, is used to spray a composite filler containing repair microcapsules together with zinc-aluminum alloy wire to form an underlayer with a thickness of 200-350 μm. The composite filler is composed of a mixture of repair microcapsules and graphene-modified zinc-aluminum powder in a specific ratio, and then coated with an amorphous alumina film using atomic layer deposition (ALD) technology to improve its thermal stability and dispersibility. The intermediate coating is an epoxy-micaceous iron oxide system with 0.5%–1.5% functionalized graphene oxide modified with a silane coupling agent. It is applied using airless spraying equipment, such as the Graco XM series, to a thickness of 300–450 μm. The topcoat is a fluorocarbon resin or polysiloxane system, with a thickness of 80–150 μm. After coating, it is cured using a portable high-intensity pulsed light (HIPL) system, such as the Xenon Sinteron IPL system, with an energy density of 5–15 J / cm² and a pulse width of 1–5 ms. This method significantly improves the coating's corrosion resistance, mechanical strength, and service life in both splash and full immersion zones, matching its 25-year design life for wind farms.

[0045] In another embodiment of the present invention, the offshore wind power foundation anti-corrosion construction method includes a method for preparing composite filler containing repair microcapsules, specifically as follows: S1. Using the sharp-hole coagulation bath method, an aqueous solution of sodium alginate containing fluorinated ceric acid corrosion inhibitor is used as the core material, and an organic solution of pH-responsive polymer, such as ethyl cellulose or cellulose acetate, is used as the wall material. The core material and wall material are dripped together into a calcium chloride coagulation bath through a dual-channel nozzle to form a microcapsule preform. The microcapsule preform is then transferred to an acetic acid solution, and the wall material is further solidified and cross-linked through interfacial polymerization. After washing and freeze-drying, spherical repair microcapsules with a particle size distribution between 50 and 150 μm are obtained. S2. Using chemical vapor deposition (CVD), zinc-aluminum alloy powder is heated to 500-800°C in a fluidized bed reactor, and carbon-containing precursor gas is introduced. The carbon atoms generated by the cracking of the carbon-containing precursor gas are deposited and graphitized on the surface of the powder particles by the catalytic effect of the zinc-aluminum alloy powder, forming a graphene-coated composite powder. S3. The repair microcapsules obtained in step S1 and the graphene-modified zinc-aluminum powder obtained in step S2 are mechanically mixed at a mass ratio of 1:8~15. After mixing, an amorphous alumina film with a thickness of 5~20nm is uniformly deposited on the surface of the mixed composite filler using atomic layer deposition (ALD) technology. The composite filler, after ALD treatment, is fed into the jet of a high-speed electric arc spray gun simultaneously with the zinc-aluminum alloy wire through a powder feeder, and together they are deposited to form a self-healing zinc-aluminum alloy composite underlayer.

[0046] This embodiment further specifies the preparation method of the composite filler. The repair microcapsules are prepared using the sharp-hole-coagulation bath method: using sodium alginate aqueous solution containing fluorinated ceric acid corrosion inhibitor as the core material and an organic solution of ethyl cellulose or cellulose acetate as the wall material, the microcapsules are dropwise added to a calcium chloride coagulation bath through a dual-channel nozzle such as the MicroNics CNC microcapsule preparation system to form a preliminary blank, which is then transferred to an acetic acid solution for further cross-linking and curing. After washing and freeze-drying, microcapsules with a particle size of 50~150μm are obtained. Graphene-modified zinc-aluminum powder is prepared by chemical vapor deposition (CVD): in a fluidized bed reactor such as the CVD-800, the zinc-aluminum alloy powder is heated to 500~800℃, and carbon-containing precursor gases such as methane or ethylene are introduced. Under catalysis, a graphene coating layer is formed on the powder surface. The aforementioned microcapsules and graphene-modified powder were mechanically mixed at a mass ratio of 1:8~15 in a high-speed mixer, such as a V-type mixer. Then, using an atomic layer deposition system such as the Beneq TFS-200, with trimethylaluminum and water as precursors, a 5~20 nm amorphous alumina film was deposited at 100~150℃ and 100~300 Pa. This composite filler was simultaneously fed into an arc spray gun along with zinc-aluminum alloy wire via a powder feeder, together forming a self-healing metal underlayer.

[0047] In another embodiment of the present invention, the offshore wind power foundation anti-corrosion construction method, before applying the epoxy micaceous iron oxide intermediate layer in step three, involves sealing the self-healing zinc-aluminum alloy substrate. Specifically, a nano-silica sol penetrating liquid diluted to a solid content of 15-25% is applied to the surface of the self-healing zinc-aluminum alloy substrate using an airless spraying process to form a transition layer with a thickness of 5-15 μm. The nano-silica sol has a particle size range of 10-20 nm and a pH value of 8.5-9.5. The transition layer is then forcibly dried at 50-60°C for 10-15 minutes before the epoxy micaceous iron oxide intermediate layer is applied.

[0048] This embodiment relates to a sealing treatment for a self-healing zinc-aluminum alloy substrate. Before coating the epoxy micaceous iron oxide intermediate layer, a nano-silica sol penetrating liquid with a solid content of 15-25%, a particle size of 10-20 nm, and a pH of 8.5-9.5 is applied to the substrate surface using an airless spraying device such as Graco Ultramax II to form a transition layer 5-15 μm thick. The nano-silica sol can be a Ludox series product or a similar commercial product. After spraying, it is forced to dry in a hot air circulating oven at 50-60°C for 10-15 minutes to form a dense inorganic film layer, effectively sealing the pores of the substrate and enhancing the adhesion and compatibility with the intermediate layer.

[0049] In another embodiment of the present invention, in the offshore wind power foundation anti-corrosion construction method, in step four, after the surface coating is completed and before scanning and curing with a portable high-intensity pulsed light curing device, a pulsed ultraviolet laser beam with a wavelength of 355-405nm is used to scan the coating surface at a scanning speed of 10-50mm / s and a pulse frequency of 5-20kHz, and the laser energy density is controlled at 50-150mJ / cm²; the scanning path of the pulsed ultraviolet laser beam forms an angle of 45-90° with the scanning path of the subsequent high-intensity pulsed light curing device.

[0050] This embodiment is limited to pretreating the coating surface using pulsed ultraviolet laser after the topcoat is applied and before IPL curing. An ultraviolet laser device, such as an Nd:YAG laser, with a wavelength of 355–405 nm, is used to scan the surface at a scanning speed of 10–50 mm / s, a pulse frequency of 5–20 kHz, and an energy density of 50–150 mJ / cm². The scanning path forms a 45–90° angle with the subsequent IPL scanning path. This treatment removes surface contaminants, activates functional groups, increases surface roughness, promotes the bonding between the topcoat and intermediate layers, and enhances the absorption and penetration of IPL energy.

[0051] In another embodiment of the present invention, the specific process of mechanical mixing in step S3 of the offshore wind power foundation anti-corrosion construction method is as follows: the repair microcapsules obtained in step S1 and the graphene-modified zinc-aluminum powder obtained in step S2 are placed in a high-speed mixer, heated to 50-70°C and stirred; then, 0.5-2.0% of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, accounting for 0.5-2.0% of the total mass of the composite filler, is dissolved in anhydrous ethanol to prepare a solution, and sprayed into the mixer in the form of atomization, and stirred for 30-60 minutes at 50-70°C.

[0052] This embodiment further refines the mechanical mixing process of the composite filler. The repaired microcapsules and graphene-modified zinc-aluminum powder are placed in a high-speed mixer, heated to 50-70°C, and stirred. Subsequently, bis-[γ-(triethoxysilyl)propyl]tetrasulfide, such as Si-69 coupling agent, is dissolved in anhydrous ethanol at 0.5-2.0% of the total mass of the composite filler and sprayed into the mixer in atomized form. Stirring continues at 50-70°C for 30-60 minutes. This process promotes surface modification of the filler particles, enhances the interfacial bonding between the microcapsules and powder, and improves their dispersion stability and functionality in the coating.

[0053] In another embodiment of the present invention, the offshore wind power foundation anti-corrosion construction method, after step three and before step four, involves treating the surface of the epoxy micaceous iron oxide intermediate layer with a silane coupling agent. Specifically, the silane coupling agent is diluted to a 1-3% aqueous solution and applied to the surface of the epoxy micaceous iron oxide intermediate layer by spraying. After standing for 5-10 minutes, the topcoat is then applied.

[0054] This embodiment involves treating the surface of an epoxy micaceous iron oxide interlayer with a silane coupling agent. Before applying the topcoat, a silane coupling agent, such as KH-550 or KH-560, is diluted to a 1-3% aqueous solution and uniformly applied to the interlayer surface using a spraying device. The solution is allowed to stand for 5-10 minutes to allow for complete hydrolysis and adsorption onto the surface, forming a molecular bridge layer. This treatment enhances the chemical bonding between the interlayer and the topcoat, improving interlayer adhesion and hydrolysis resistance.

[0055] In another embodiment of the present invention, in the offshore wind power foundation anti-corrosion construction method, after sandblasting and before applying the base coat, the surface roughness is detected by a non-contact three-dimensional surface profilometer. If the Ry value does not reach the range of 60-100μm, the sandblasting is repeated until the standard is met. The abrasive used for sandblasting is a mixture of steel grit and steel shot with a mixing mass ratio of 7:3, an abrasive hardness of HRC 40-50, and a particle size range of 0.5-1.2mm.

[0056] This embodiment defines the detection and control of surface roughness after sandblasting. A non-contact three-dimensional surface profilometer, such as the Keyence VR-5000, is used to detect the Ry value of the sandblasted surface. If the Ry value does not reach the 60-100 μm range, the sandblasting process is repeated until the standard is met. The sandblasting abrasive is a mixture of steel grit and steel shot at a mass ratio of 7:3, with a hardness of HRC 40-50 and a particle size of 0.5-1.2 mm. This measure ensures that the substrate surface has a uniform and suitable anchoring structure, providing optimal mechanical adhesion for the coating.

[0057] In another embodiment of the present invention, in the offshore wind power foundation anti-corrosion construction method, the specific process parameters for depositing amorphous alumina thin films using atomic layer deposition (ALD) technology in step S3 are as follows: trimethylaluminum and water are used as precursors, the deposition temperature is 100-150℃, the reaction chamber pressure is 100-300Pa, the aeration time for each ALD cycle is 0.5-1.5s, the purification time is 5-10s, and the number of cycles is 50-200.

[0058] This embodiment further defines the atomic layer deposition (ALD) process parameters. Trimethylaluminum (TMA) and water are used as precursors; the deposition temperature is 100–150°C; the chamber pressure is 100–300 Pa; the TMA aeration time in each ALD cycle is 0.5–1.5 s; the purging time is 5–10 s; and the number of cycles is 50–200. This process forms a uniform and dense amorphous alumina film on the surface of the composite filler, providing electrical insulation protection without affecting its cathodic protection function.

[0059] In another embodiment of the present invention, in the offshore wind power foundation anti-corrosion construction method, in step four, the working parameters of the portable intense pulsed light (IPL) curing equipment further include: a pulse spectrum range of 300–800 nm, a cooling time interval of 2–5 s after a single pulse, a working distance of 10–15 cm between the scanning head and the coating surface, and a scanning overlap rate of 30–50%.

[0060] This embodiment further defines the operating parameters of the intense pulsed light (IPL) curing equipment. The pulse spectrum range of the IPL equipment is 300~800nm, the cooling interval after a single pulse is 2~5 seconds, the scanning head is 10~15cm away from the coating surface, and the scanning overlap rate is 30~50%. These parameters ensure that the light energy can fully penetrate the surface layer and trigger the cross-linking reaction between the intermediate layer and the transition layer, avoiding local overheating that could lead to coating defects.

[0061] In another embodiment of the present invention, the offshore wind power foundation anti-corrosion construction method, after all coating construction and curing are completed, uses electrochemical impedance spectroscopy (EIS) to perform non-destructive testing on the coating system, with a test frequency range of 10. 5 ~10 -2 The applied AC disturbance signal amplitude is 20 mV; if the impedance modulus |Z| measured at 0.01 Hz is less than 1 × 10⁻⁶ mV; 8 If the impedance modulus is greater than Ω·cm², then the coating in that area is considered defective and needs to be marked and recoated. The impedance modulus threshold is 1×10⁻⁶. 8 Ω·cm² is set based on marine engineering coating protection level standards and long-term service data. A value below this indicates that the coating has significant defects.

[0062] This implementation method involves the final quality assessment of the coating system. Electrochemical impedance spectroscopy (EIS) equipment, such as a Gamry Reference 600+, was used for non-destructive testing of the coating, with a test frequency range of 10... 5 ~10 -2 The AC disturbance signal amplitude is 20mV at Hz. If the impedance magnitude |Z| is less than 1×10 at 0.01Hz... 8 Ω·cm 2 If a defect is detected in the area, it is determined that the area needs to be marked and recoated. This method is an effective means of quickly assessing the integrity and corrosion resistance of the coating on-site.

[0063] Example 1 A method for corrosion protection construction of offshore wind turbine foundations, the specific steps of which are as follows: Surface pretreatment: Q355B steel plates were sandblasted using a mixture of steel grit and steel shot (mass ratio 7:3) with a hardness of HRC 45 and a particle size range of 0.8-1.0 mm. After treatment, a non-contact three-dimensional surface profilometer was used to confirm that the cleanliness reached Sa 2.5 level and the surface roughness Ry was 85 μm.

[0064] Self-healing zinc-aluminum alloy undercoat: The prepared composite filler containing repair microcapsules is sprayed together with zinc-aluminum alloy wire onto the pretreated steel plate surface using a high-speed arc spraying system. The repair microcapsule areal density is approximately 1200 capsules / mm², the zinc-aluminum alloy wire is Zn-15Al, and the spraying parameters are: current 350A, voltage 32V, and spraying distance 200mm. This results in a uniform undercoat layer with a thickness of approximately 280μm.

[0065] Epoxy micaceous iron oxide intermediate layer coating: Using airless spraying equipment, an epoxy micaceous iron oxide intermediate coating with 1.0% functionalized graphene oxide is applied to the zinc-aluminum alloy substrate. The coating process is strictly controlled to achieve an intermediate layer thickness of 380μm. Curing is carried out for 7 days at a temperature of 23±2℃ and a relative humidity of 50±5%.

[0066] Topcoat application and curing: A fluorocarbon topcoat is applied over the intermediate layer, with the wet film thickness controlled at 120 μm. Immediately after topcoat application, a portable intense pulsed light (IPL) curing device is used for scanning and curing. IPL parameters are set as follows: energy density 10 J / cm². 2 The pulse width was 3ms, the spectral range was 300-800nm, the scanning head distance was 15cm, and the overlap rate was 40%. After scanning and curing, the coating was left at room temperature for 24 hours before performance testing.

[0067] Example 2 Based on Example 1, the preparation method of the composite filler containing repair microcapsules is as follows: S1. Using the sharp-hole coagulation bath method, sodium alginate aqueous solution containing fluorinated ceric acid corrosion inhibitor is used as the core material, and an organic solution of pH-responsive polymer is used as the wall material. The core material and wall material are dripped together into a calcium chloride coagulation bath through a dual-channel nozzle to form a microcapsule preform. The microcapsule preform is then transferred to an acetic acid solution, and the wall material is further solidified and cross-linked through interfacial polymerization. After washing and freeze-drying, spherical repair microcapsules are obtained. S2. Using chemical vapor deposition, zinc-aluminum alloy powder is heated to 650°C in a fluidized bed reactor, and carbon-containing precursor gas is introduced. The carbon atoms generated by the cracking of the carbon-containing precursor gas are deposited and graphitized on the surface of the powder particles by the catalytic effect of the zinc-aluminum alloy powder, forming a graphene-coated composite powder. S3. The repair microcapsules obtained in step S1 and the graphene-modified zinc-aluminum powder obtained in step S2 are mechanically mixed at a mass ratio of 1:12. After mixing, an amorphous alumina film with a thickness of 18 nm is uniformly deposited on the surface of the mixed composite filler using atomic layer deposition technology. The composite filler after ALD treatment is fed into the jet of the high-speed electric arc spray gun simultaneously with the zinc-aluminum alloy wire through the powder feeder, and together they are deposited to form a self-healing zinc-aluminum alloy composite underlayer. In step S3, the specific process parameters for depositing amorphous alumina thin films using atomic layer deposition technology are as follows: trimethylaluminum and water are used as precursors, the deposition temperature is 130°C, the reaction chamber pressure is 200Pa, the aeration time for each ALD cycle is 1.0s, the purification time is 8s, and the number of cycles is 130.

[0068] The remaining experimental procedures and parameters are the same as in Example 1.

[0069] Example 3 Based on Example 2, before coating the epoxy micaceous iron oxide intermediate layer in step three, the self-healing zinc-aluminum alloy substrate is sealed. Specifically, a nano-silica sol diluted to 20% solids content is applied to the surface of the self-healing zinc-aluminum alloy substrate using an airless spraying process to form a transition layer with a thickness of 10 μm. The nano-silica sol has a particle size range of 15 nm and a pH value of 9. The transition layer is forced to dry at 55°C for 13 minutes before coating the epoxy micaceous iron oxide intermediate layer.

[0070] The remaining experimental processes and parameters are the same as in Example 2.

[0071] Example 4 Based on Example 3, in step four, after the surface coating is completed and before scanning and curing using a portable intense pulsed light curing device, a pulsed ultraviolet laser beam with a wavelength of 375nm is used to scan the coating surface at a scanning speed of 30mm / s and a pulse frequency of 14kHz, with the laser energy density controlled at 100mJ / cm²; the scanning path of the pulsed ultraviolet laser beam forms a 65° angle with the scanning path of the subsequent intense pulsed light curing device.

[0072] The remaining experimental procedures and parameters are the same as in Example 3.

[0073] Example 5 Based on Example 4, the specific process of mechanical mixing in step S3 is as follows: the repair microcapsules obtained in step S1 and the graphene-modified zinc-aluminum powder obtained in step S2 are placed in a high-speed mixer, heated to 60°C and stirred; then, 1.3% of the total mass of the composite filler, bis-[γ-(triethoxysilyl)propyl]tetrasulfide is dissolved in anhydrous ethanol to prepare a solution, and sprayed into the mixer in the form of atomization, and stirred at 60°C for 45 min.

[0074] The remaining experimental procedures and parameters are the same as in Example 4.

[0075] Example 6 Based on Example 5, after step 3 is completed and before step 4 begins, the surface of the epoxy micaceous iron intermediate layer is treated with a silane coupling agent. Specifically, the silane coupling agent is diluted to a 1-3% aqueous solution and applied to the surface of the epoxy micaceous iron intermediate layer by spraying. After standing for 5-10 minutes, the topcoat is then applied.

[0076] The remaining experimental procedures and parameters are the same as in Example 5.

[0077] Example 7 Based on Example 6, In step one, after sandblasting to remove rust and before applying the base coat, the surface roughness is tested using a non-contact three-dimensional surface profilometer. If the Ry value does not reach the range of 80μm, the sandblasting is repeated until the standard is met. The abrasive used for sandblasting is a mixture of steel grit and steel shot with a mixing mass ratio of 7:3, an abrasive hardness of HRC45, and a particle size range of 0.8mm.

[0078] The remaining experimental procedures and parameters are the same as in Example 6.

[0079] Example 8 Based on Example 7, in step four, the operating parameters of the portable intense pulsed light curing device also include: a pulse spectrum range of 550 nm, a cooling time interval after a single pulse of 4 s, a working distance of 13 cm between the scanning head and the coating surface, and a scanning overlap rate of 40%. After all coating applications and curing were completed, electrochemical impedance spectroscopy was used to perform non-destructive testing on the coating system, with a test frequency range of 10. 5 ~10 -2 The applied AC disturbance signal amplitude is 20mV; if the impedance modulus |Z| measured at a frequency of 0.01Hz is less than 1×10⁻⁶, the disturbance signal amplitude is 20mV. 8 If the value is Ω·cm², then the coating in that area is considered defective and needs to be marked and recoated.

[0080] Comparative Example 1: Traditional Anti-corrosion Coating System This comparison model uses the most commonly used and traditional anti-corrosion coating system and construction process in the current offshore wind power field.

[0081] Surface pretreatment: exactly the same as in Example 1, sandblasted to Sa 2.5 grade, Ry 60-100μm.

[0082] Undercoat application: Apply one coat of epoxy zinc-rich primer (80% zinc powder content) using high-pressure airless spraying, achieving a dry film thickness of 80μm. Allow to cure naturally at 23±2℃ for 24 hours.

[0083] Intermediate layer coating: Spray epoxy micaceous iron oxide intermediate paint (without adding any functionalized graphene oxide), dry film thickness 350μm. Natural curing for 7 days.

[0084] Topcoat application and curing: Spray fluorocarbon topcoat with a dry film thickness of 100 μm. Allow to cure naturally for 7 days at 23±2℃ and humidity <85%.

[0085] Test case To verify the superiority of the offshore wind power foundation anti-corrosion construction method of the present invention (represented by Examples 1-8) over the traditional process (Comparative Example 1), the adhesion, neutral salt spray resistance, impact resistance, cathodic disbondment resistance and electrochemical impedance modulus of the coating were tested and analyzed, and the results are shown in Table 1.

[0086] I. Sample Preparation Experimental group: Coating systems prepared according to the processes of Examples 1 to 8, respectively; Control group: Traditional coating system prepared according to the process of Comparative Example 1; Base material: Q355B steel plate, dimensions 150mm×100mm×6mm; Number of samples per group: n = 3, take the average value.

[0087] II. Test Methods and Calculation Methods 1. Adhesion test Method: The cross-cut adhesion test (1mm spacing) and the pull-off test (PosiTest AT-A adhesion tester) were combined according to GB / T 5210-2006. Calculation: Cross-cutting rating (0~5, 0 being the best); tensile test to record tensile strength (MPa) and failure type (cohesive / attachment failure).

[0088] 2. Neutral salt spray resistance test Method: Neutral salt spray test (5% NaCl, 35℃) was conducted according to GB / T 1771-2007. Cycle: 3000 hours; Assessment: Observe the blistering, corrosion and peeling of the coating surface and rate it according to GB / T 1766-2008; record the corrosion width (mm) on both sides of the scratch.

[0089] 3. Impact resistance test Method: Drop ball impact test according to GB / T 20624.2-2006; Parameters: 1kg steel ball, 50cm height, observe whether the coating cracks or peels after impact; Evaluation: Pass / Fail, record the minimum cracking energy (J).

[0090] 4. Resistance to cathode stripping test Method: The cathode stripping test was performed according to GB / T 7790-2008; Parameters: -1.5V vs. SCE, 3% NaCl solution, 30℃, 28 days; Assessment: Measure the peel radius (mm) and calculate the peel area.

[0091] 5. Electrochemical Impedance Spectroscopy (EIS) Testing Methods: A Gamry Reference 600+ electrochemical workstation with a three-electrode system (saturated calomel electrode reference, platinum sheet auxiliary) was used. Parameters: Frequency range 10 5 ~ 10 -2 Hz, amplitude 20mV; Evaluation: Record the impedance magnitude |Z| (Ω·cm) at 0.01 Hz. 2 ), to evaluate the shielding performance of the coating.

[0092] Table 1 Test Results As can be seen from the experimental data in Table 1, the offshore wind power foundation anti-corrosion construction method proposed in this invention (Examples 1-8) is significantly superior to the traditional anti-corrosion coating system (Comparative Example 1) in all key performance indicators. Adhesion test results show that the average adhesion of the traditional coating is 10.2 MPa, while the adhesion of Examples 1-8 of this invention increases progressively from 14.5 MPa to 18.5 MPa, with the highest increase exceeding 80%. This significant improvement not only reflects the enhanced mechanical bonding between the coating and the substrate but also the optimized interfacial bonding between the multilayer coating system. In particular, the steps of nano-silica sol sealing treatment, silane coupling agent modification, and ultraviolet laser activation significantly enhance the interlayer chemical bonding and physical anchoring effect.

[0093] In terms of corrosion resistance, the corrosion width data after 3000 hours of neutral salt spray testing is particularly outstanding. Comparative Example 1 showed a corrosion width of 4.5 mm, while Example 8 of this invention only showed 1.2 mm, a reduction of over 73%. This result demonstrates that the self-healing underlayer, graphene-reinforced intermediate layer, and intense pulsed light-cured top layer system constructed in this invention significantly delays the corrosion of corrosive media (such as Cl-). - The coating effectively inhibited the corrosion propagation of the metal substrate beneath it by reducing the penetration rate of the coating. Especially in simulated splash zones, the coating system exhibited excellent barrier performance and self-healing capabilities. The repair microcapsules released corrosion inhibitors upon local pH changes, working synergistically with the shielding effect of graphene to jointly prevent the corrosion reaction from proceeding.

[0094] The improved impact resistance and cathodic disbondment resistance further validated the mechanical strength and interfacial stability of the coating system of this invention. No impact cracking occurred in any of the embodiments, while significant cracking occurred in Comparative Example 1; the cathodic disbondment radius decreased from 8.2 mm in Comparative Example 1 to 3.5 mm in Example 8, a reduction of 57%. These results demonstrate that this invention, through the uniform dispersion of composite fillers, the densification treatment of the transition layer, and the enhanced curing of the surface layer, significantly improves the toughness and bonding strength of the coating, effectively resisting the disbondment stress caused by mechanical impact and cathodic polarization.

[0095] Chemical impedance spectroscopy (EIS) results showed that the impedance modulus of Comparative Example 1 at 0.01 Hz was only 0.32 × 10⁻⁶. 8 Ω·cm 2 The figure for Embodiment 8 of the present invention is as high as 2.50 × 10⁸. 8 Ω·cm 2The impedance is improved by nearly 7 times. This indicator directly reflects the shielding performance and defect status of the coating system. The significant increase in value indicates that the coating of this invention can maintain extremely high impedance in the low-frequency region, demonstrating its dense structure, few defects, good interfacial bonding, and potential for long-term corrosion protection. This result far exceeds industry expectations, especially considering that such a high impedance value is usually difficult to achieve with traditional coating systems in harsh marine environments.

[0096] In summary, this invention achieves a systematic improvement in coating performance through multi-level material design and process innovation, including key steps such as microcapsule self-healing mechanism, graphene reinforcement, nano-silica sol encapsulation, ultraviolet laser activation, and intense pulsed light curing. The various performance indicators not only significantly outperform existing technologies but also exhibit near-order-of-magnitude improvements in key indicators such as impedance modulus, fully demonstrating the outstanding technological advancement and application potential of this invention in the field of corrosion protection for offshore wind power foundations.

[0097] The number of devices and processing scale described herein are for the purpose of simplifying the description of the invention. Applications, modifications, and variations of the invention will be readily apparent to those skilled in the art.

[0098] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details.

Claims

1. A method for corrosion protection construction of offshore wind turbine foundations, characterized in that, Includes the following steps: Step 1: Sandblast the outer surface of the offshore wind power foundation steel structure to remove rust, achieving a cleanliness level of Sa2.5 and a surface roughness of Ry60~100μm; Step 2: Apply a self-healing zinc-aluminum alloy underlayer to the splash zone and full immersion zone of the pretreated steel structure. This underlayer is formed by high-speed arc spraying of a composite filler containing repair microcapsules together with zinc-aluminum alloy wire. The spraying thickness is 200-350μm. The composite filler containing repair microcapsules is composed of microcapsules coated with corrosion inhibitors and graphene-modified zinc-aluminum powder. Step 3: Coat an epoxy micaceous iron oxide intermediate layer onto the zinc-aluminum alloy base layer. The epoxy micaceous iron oxide intermediate layer coating contains functionalized graphene oxide sheets that have been surface-modified with a silane coupling agent. The amount of graphene oxide added is 0.5% to 1.5% of the total mass of the epoxy micaceous iron oxide coating. The thickness of the epoxy micaceous iron oxide intermediate layer is 300 to 450 μm. Step 4: Coat the epoxy micaceous iron oxide intermediate layer with a fluorocarbon resin or polysiloxane top layer with a thickness of 80-150 μm. After the topcoat is applied, a portable high-intensity pulsed light curing device is used to scan and cure the coating system. The energy density of the high-intensity pulsed light is 5-15 J / cm², and the pulse width is 1-5 ms.

2. The offshore wind power foundation anti-corrosion construction method as described in claim 1, characterized in that, The preparation method of the composite filler containing repair microcapsules is as follows: S1. Using the sharp-hole coagulation bath method, sodium alginate aqueous solution containing fluorinated ceric acid corrosion inhibitor is used as the core material, and an organic solution of pH-responsive polymer is used as the wall material. The core material and wall material are dripped together into a calcium chloride coagulation bath through a dual-channel nozzle to form a microcapsule preform. The microcapsule preform is then transferred to an acetic acid solution, and the wall material is further solidified and cross-linked through interfacial polymerization. After washing and freeze-drying, spherical repair microcapsules are obtained. S2. Using chemical vapor deposition, zinc-aluminum alloy powder is heated to 500-800℃ in a fluidized bed reactor, and carbon-containing precursor gas is introduced. The carbon atoms generated by the cracking of the carbon-containing precursor gas are deposited and graphitized on the surface of the powder particles by the catalytic effect of the zinc-aluminum alloy powder, forming a graphene-coated composite powder. S3. The repair microcapsules obtained in step S1 and the graphene-modified zinc-aluminum powder obtained in step S2 are mechanically mixed at a mass ratio of 1:8~15. After mixing, an amorphous alumina film with a thickness of 5~20nm is uniformly deposited on the surface of the mixed composite filler using atomic layer deposition technology. The composite filler, after ALD treatment, is fed into the jet of a high-speed electric arc spray gun simultaneously with the zinc-aluminum alloy wire through a powder feeder, and together they are deposited to form a self-healing zinc-aluminum alloy composite underlayer.

3. The offshore wind power foundation anti-corrosion construction method as described in claim 1, characterized in that, Before applying the epoxy micaceous iron oxide intermediate layer in step three, the self-healing zinc-aluminum alloy substrate is sealed. Specifically, a nano-silica sol penetrating liquid diluted to a solid content of 15-25% is applied to the surface of the self-healing zinc-aluminum alloy substrate using an airless spraying process to form a transition layer with a thickness of 5-15μm. The nano-silica sol has a particle size range of 10-20nm and a pH value of 8.5-9.

5. The transition layer is then forced to dry at 50-60℃ for 10-15 minutes before the epoxy micaceous iron oxide intermediate layer is applied.

4. The offshore wind power foundation anti-corrosion construction method as described in claim 1, characterized in that, In step four, after the surface coating is completed and before scanning and curing using a portable intense pulsed light curing device, a pulsed ultraviolet laser beam with a wavelength of 355–405 nm is used to scan the coating surface at a scanning speed of 10–50 mm / s and a pulse frequency of 5–20 kHz. The laser energy density is controlled at 50–150 mJ / cm². The scanning path of the pulsed ultraviolet laser beam forms an angle of 45–90° with the scanning path of the subsequent intense pulsed light curing device.

5. The offshore wind power foundation anti-corrosion construction method as described in claim 2, characterized in that, The specific process of mechanical mixing in step S3 is as follows: the repair microcapsules obtained in step S1 and the graphene-modified zinc-aluminum powder obtained in step S2 are placed in a high-speed mixer, heated to 50-70°C and stirred; then, 0.5-2.0% of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, accounting for 0.5-2.0% of the total mass of the composite filler, is dissolved in anhydrous ethanol to prepare a solution, which is then sprayed into the mixer in the form of atomization, and stirred for 30-60 minutes at 50-70°C.

6. The offshore wind power foundation anti-corrosion construction method as described in claim 1, characterized in that, After step three is completed and before step four begins, the surface of the epoxy micaceous iron oxide intermediate layer is treated with a silane coupling agent. Specifically, the silane coupling agent is diluted to a 1-3% aqueous solution and applied to the surface of the epoxy micaceous iron oxide intermediate layer by spraying. After standing for 5-10 minutes, the topcoat is then applied.

7. The offshore wind power foundation anti-corrosion construction method as described in claim 1, characterized in that, In step one, after sandblasting to remove rust and before applying the base coat, the surface roughness is tested using a non-contact three-dimensional surface profilometer. If the Ry value does not reach the range of 60-100μm, the sandblasting is repeated until the standard is met. The abrasive used for sandblasting is a mixture of steel grit and steel shot with a mixing mass ratio of 7:3, an abrasive hardness of HRC40-50, and a particle size range of 0.5-1.2mm.

8. The offshore wind power foundation anti-corrosion construction method as described in claim 2, characterized in that, In step S3, the specific process parameters for depositing amorphous alumina thin films using atomic layer deposition technology are as follows: trimethylaluminum and water are used as precursors, the deposition temperature is 100-150℃, the reaction chamber pressure is 100-300Pa, the aeration time for each ALD cycle is 0.5-1.5s, the purification time is 5-10s, and the number of cycles is 50-200.

9. The offshore wind power foundation anti-corrosion construction method as described in claim 1, characterized in that, In step four, the operating parameters of the portable intense pulsed light curing device also include: a pulse spectrum range of 300–800 nm, a cooling time interval of 2–5 s after a single pulse, a working distance of 10–15 cm between the scanning head and the coating surface, and a scanning overlap rate of 30–50%.

10. The offshore wind power foundation anti-corrosion construction method as described in claim 1, characterized in that, After all coating applications and curing were completed, electrochemical impedance spectroscopy was used to perform non-destructive testing on the coating system, with a test frequency range of 10. 5 ~10 -2 The applied AC disturbance signal amplitude is 20mV; if the impedance modulus |Z| measured at a frequency of 0.01Hz is less than 1×10⁻⁶, the disturbance signal amplitude is 20mV. 8 If the value is Ω·cm², then the coating in that area is considered defective and needs to be marked and recoated.